blaCTX-M-27–Encoding Escherichia coli Sequence Type 131 Lineage C1-M27 Clone in Clinical Isolates, Germany - Hiren Ghosh; Swapnil Doijad; Linda Falgenhauer; Moritz Fritzenwanker; Can Imirzalioglu; Trinad Chakraborty (Emerging Infectious Diseases, 2017)
We examined extended-spectrum β-lactamase–producing isolates from livestock, humans, companion animals, food, and the environment during 2009–2016 in Germany for the presence of CTX-M-27 allele within Escherichia coli sequence type (ST) 131. E. coli ST131 C1-M27 was exclusively present in humans; its incidence increased from 0% in 2009 to 45% in 2016.